TINJAUAN YURIDIS TERHADAP TANGGUNG JAWAB PEMILIK MOBIL PRIBADI YANG DIGUNAKAN SEBAGAI ANGKUTAN UMUM MENURUT PERATURAN UNDANG-UNDANG NOMOR 22 TAHUN 2009 TENTANG LALU LINTAS DAN ANGKUTAN JALAN - Wenky Berlinto (Journal of Law ( Jurnal Ilmu Hukum ), 2021)
AbstractTransportation is a means that many people need since ancient times in carrying out its activities, which are realized in the form of transportation. Transportation is divided into the transportation of people and/or goods intended for public or private use. This research was conducted to find out how the legal efforts of the Department of Transportation and related agencies in preventing Dark Taxi transportation and how Legal sanctions on private cars used as public transport in Law No. 22 of 2009 concerning Road Traffic and Transport. By using normative and empirical juridical research methods. Based on the results of the study, Legal Efforts from the Transportation Department want relevant agencies in preventing Dark Taxi transportation to be considered not optimal in eradicating illegal taxis, due to weak supervision and the number of members in charge of monitoring is still minimal so that drivers and owners of illegal taxi vehicles are freer to carry out their actions without close supervision from the Transportation Department and the Police. Legal Sanctions on private cars used as public transportation in Law no. 22 of 2009 concerning Traffic and Road Transportation according to Article 304 is considered ineffective in its implementation because many violators have been arrested several times with this same case indicating that the Act does not deter the perpetrators in carrying out their actions as illegal taxi drivers.